2022
DOI: 10.3390/ani12141776
|View full text |Cite
|
Sign up to set email alerts
|

CFD Study of a Tunnel-Ventilated Compost-Bedded Pack Barn Integrating an Evaporative Pad Cooling System

Abstract: Evaporative cooling is one of the most efficient techniques to reduce heat stress in cows in agricultural facilities. Additionally, compost-bedded pack barn has been shown to improve the welfare and production of cows. Two techniques were combined and analysed by developing a computational fluid dynamics (CFD) model of a tunnel-ventilated compost-bedded packed barn that integrated the heat and airflow dynamics of an evaporative pad cooling system. This allowed us to study the distribution of dry-bulb temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…Vega et al [59] reported a first approach to modeling and simulating the thermal distribution inside a tunnel-ventilated CBP facility with an evaporative cooling system located in a tropical environment, using computational fluid dynamics (CFD). They observed that the average difference in dry-bulb temperature between the external and internal conditions was 2.1 to 5.8 °C.…”
Section: Negative Pressure Ventilation Systemsmentioning
confidence: 99%
“…Vega et al [59] reported a first approach to modeling and simulating the thermal distribution inside a tunnel-ventilated CBP facility with an evaporative cooling system located in a tropical environment, using computational fluid dynamics (CFD). They observed that the average difference in dry-bulb temperature between the external and internal conditions was 2.1 to 5.8 °C.…”
Section: Negative Pressure Ventilation Systemsmentioning
confidence: 99%
“…Vega et al [ 53 ] reported a first approach to modeling and simulating the thermal distribution inside a tunnel-ventilated CBP facility located in a tropical environment with an evaporative cooling system using computational fluid dynamics (CFD). They observed that the average difference in the dry-bulb temperature between the external and internal conditions was from 2.1 to 5.8 °C.…”
Section: Compost-bedded Pack Barn Systemsmentioning
confidence: 99%
“…Vega et al [53] reported a first approach to modeling and simulating the thermal distribution inside a tunnel-ventilated CBP facility located in a tropical environment with an evaporative cooling system using computational fluid dynamics (CFD). They observed that the average difference in the dry-bulb temperature between the external and internal con-ditions was from 2.1 to 5.8 • C. They recommended increasing the airflow velocity to above 3 m•s −1 when the external dry-bulb temperature and the relative humidity simultaneously exceed 30 • C and 55%, respectively.…”
Section: Negative-pressure Ventilation Systemsmentioning
confidence: 99%
“…Usually, the software used for CFD simulations is commercial. Among these, for modeling animal facilities can be highlighted the Ansys ® CFX [28,29,36,[40][41][42][43], Ansys ® Fluent [15,16,19,20,31,35,39,[44][45][46], and the Simcenter STAR-CCM+ [13,47].…”
Section: Software Usedmentioning
confidence: 99%
“…Due to its versatility, the CFD technique has been increasingly applied for modeling airflow and moisture conditions in agricultural facilities, being considered an ideal complement for field measurements [27]. In dairy cattle facilities, particularly the use of CFD for heat and mass transfer modeling has been widely used to evaluate and understand the behavior of thermal environmental conditions [14][15][16]19,20,26,[28][29][30][31]. The expressive majority of CFD modeling studies in dairy cattle facilities were carried out on typical conditions of collective housing systems in individual stalls (Free Stall).…”
Section: Introductionmentioning
confidence: 99%